2014
DOI: 10.4314/njp.v41i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of urinary tract infection and antimicrobial sensitivities in under-five children in Enugu

Abstract: Background: Urinary tract infection (UTI) is one of the serious bacterial infections in febrile young children, which may cause chronic morbidities. Studies from different parts of Nigeria have shown varying pattern in its bacteriology and antibiotic sensitivities. Antimicrobial resistance rate among uropathogens is an increasing problem limiting therapeutic options, and underscores the need to determine local bacteriological pattern that will guide empiric antibiotic choices. Objectives: To identify the bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…28 Third generation Cephalosporins were found to be having better coverage with relatively low reported resistance in different studies and were suggested for the empiric treatment of febrile UTI. 5,10 But in this study, Cephalosporins had higher resistance rates to E. coli and others. This reveals grave therapeutic implications for patient care, as many traditional antibiotics, which are affordable and easily available, are no longer useful.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…28 Third generation Cephalosporins were found to be having better coverage with relatively low reported resistance in different studies and were suggested for the empiric treatment of febrile UTI. 5,10 But in this study, Cephalosporins had higher resistance rates to E. coli and others. This reveals grave therapeutic implications for patient care, as many traditional antibiotics, which are affordable and easily available, are no longer useful.…”
Section: Discussionmentioning
confidence: 93%
“…Inspite of good sensitivity of uropathogens to Nitrofuratoin, it may not have good compliance in practice due to its bitterness. 5 Nevertheless, some studies recommended Nitrofurantoin as the first choice among oral antibiotics for prophylaxis and treatment of UTI in children due to higher sensitivity. 28 Third generation Cephalosporins were found to be having better coverage with relatively low reported resistance in different studies and were suggested for the empiric treatment of febrile UTI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Third generation cephalosporins were found to be having better coverage with relatively low reported resistance in different studies and were suggested for the empiric treatment of febrile UTI. 13,16 But this study showed increased resistance of E. coli to ceftriaxone and other cephalosporins like cephradin, cefuroxime, cefixime. Most of these antibiotics are used empirically in Bangladesh and resistance of E. coli to these commonly used antibiotics appears to be alarming.…”
Section: Discussionmentioning
confidence: 72%